Etravirine Pharmacokinetics in HIV-Infected Pregnant Women - Mulligan, Nikki; Schalkwijk, Stein; Best, Brookie M.; Colbers, Angela; Wang, Jiajia; Capparelli, Edmund V.; Moltó, José; Stek, Alice M.; Taylor, Graham; Smith, Elizabeth; Hidalgo Tenorio, Carmen; Chakhtoura, Nahida; et al. (Frontiers in Pharmacology, 2016)
Background: The study goal was to describe etravirine pharmacokinetics during pregnancy and postpartum in HIV-infected women. Methods: IMPAACT P1026s and PANNA are on-going, nonrandomized, open-label, parallel-group, multi-center phase-IV prospective studies in HIV-infected pregnant women. Intensive steady-state 12 or 24 hour pharmacokinetic profiles were performed from 2nd trimester through postpartum. Etravirine was measured at two labs using validated ultra performance liquid chromatography (detection limits: 0.020 mcg/mL and 0.026 mcg/mL). Results: Fifteen women took etravirine 200 mg twice-daily dosing and one took 400 mg once-daily. Etravirine AUC0-12 was significantly higher in the 3rd trimester compared to paired postpartum data by 45% (median 8.3 mcg*hr/mL versus 5.7 mcg*hr/mL, p = 0.086). Etravirine apparent oral clearance was significantly lower in the 3rd trimester of pregnancy compared to paired postpartum data (median 24 L/h versus 35 L/h, p = 0.038). The median ratio of cord blood to maternal plasma concentration at delivery was 0.56 (range: 0.19 - 4.25) and no perinatal transmission occurred. Conclusion: Etravirine apparent oral clearance is reduced and exposure increased during the third trimester of pregnancy. Based on prior dose-ranging and safety data, no dose adjustment is necessary for maternal health but the effects of etravirine in utero are unknown. Maternal health and infant outcomes should be closely monitored until further infant safety data are available. The IMPAACT protocol P1026s and PANNA study are registered at ClinicalTrials.gov under NCT00042289 and NCT00825929.